PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA KELAS IV MELALUI MEDIA BERBASIS DOLANAN ANAK DI SD NEGERI WIROSABAN - Susanti, Siti; Setiana, Dafid Slamet (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
This study aims to describe the process of learning mathematics using child-based media can improve the understanding of mathematical concepts in fourth-grade students at Wirosaban State Elementary School. This type of research is Classroom Action Research (CAR). The subjects of this study were 15 Class IV students of Wirosaban State Elementary School. Data collection techniques in this study used observation, test, and documentation techniques. Data analysis techniques in this research are qualitative and quantitative descriptive techniques. The results showed the use of child-based media can improve the understanding of mathematical concepts in fourth-grade students of Wirosaban State Elementary School. This can be seen from the results of the pre-cycle measures obtained an average value of 59.9 with the completeness of 26.7% and an average achievement indicator of 59.9%. In the first cycle, the average value of 68.3 was obtained with 60% completeness and the average achievement of concept understanding indicators was 68.3%. In the second cycle, an average value of 78.8 was obtained with 80% completeness and the average achievement of concept understanding indicators was 78.8%.